Unfair teachers, unhappy students: longitudinal associations of perceived teacher relational unfairness with adolescent peer aggression and school satisfaction - Gini, Gianluca; Angelini, Federica; Pozzoli, Tiziana (Frontiers in Psychology, 2024)
Introduction Teacher relational unfairness is a significant risk factor for students’ physical and mental well-being, especially during adolescence. However, school psychology research has not yet fully analyzed the links between teacher unfairness and important indicators of school experience and wellbeing, including peer aggression and school satisfaction. Even less evidence does exist with longitudinal, multilevel data. Methods The present study tested the prospective relations between Fall perceived teacher unfairness and Spring reactive and proactive aggression, and school satisfaction. At T1, participants were 1,299 students (48.3% girls, mean age = 13.6 years, SD = 1.1) attending 67 classrooms in Italian public schools, whereas 1,227 students participated in the second wave 6 months later. Results Multilevel regressions showed that, at the individual level, T1 perceived teacher unfairness positively predicted T2 reactive and proactive aggression, and negatively predicted school satisfaction. At the class-level, T1 class teacher unfairness explained between-class variability in T2 school satisfaction, but not variability in peer aggression. Discussion The findings expand current knowledge about the role of teacher unfairness with the classroom and have implications for interventions at school.